Liquid biopsy in organ damage: introduction of an innovative tool for assessing the complexity of blunt splenic injury - Aliona Wöhler; Bingduo Wang; Robert Schwab; Veronika Lukacs-Kornek; Arnulf G. Willms; Miroslaw T. Kornek (European Journal of Medical Research)
Abstract Liquid biomarkers are essential in trauma cases and critical care and offer valuable insights into the extent of injury, prognostic predictions, and treatment guidance. They can help assess the severity of organ damage (OD), assist in treatment decisions and forecast patient outcomes. Notably, small extracellular vesicles, particularly those involved in splenic trauma, have been overlooked. Here, we reanalyzed our data and explored whether monocyte-derived small EVs are correlated with AAST score (American Association for the Surgery of Trauma) scoring and are sensitive enough to distinguish the severity of splenic trauma in our explorative study. There was a correlation between monocyte-derived small extracellular vesicles (EVs) and the AAST score (rSp = 0.82, p < 0.001). Specifically, we observed that blood-borne small EVs originating from monocytes (CD9+CD14+ sEVs) were directly correlated with AAST scores. These EVs were found to be significantly elevated in patients with complex spleen injuries (AAST I–IV with hemodynamic instability and need for operative management) in an incremental manner; these patients were typically classified as AAST grade II or higher, which frequently included accompanying solid organ injuries. Our initial discovery shows great promise and warrants further exploration. This could pave a novel future path for a new critical care management approach for splenic injuries. There may also be synergistic effects when combined with extended focused assessment with sonography in trauma (E-FAST) sonography, particularly in triage scenarios, where resource constraints prevent immediate access to a CT scan.